A study on knowledge and practice on post cardiac arrest care among healthcare providers working in Emergency Department in Kelantan - Ismail, Norhayati (2016)
INTRODUCTION 2010 American Heart Association (AHA) guidelines on CPR and ECC had created the fifth link of the chain of survival which is integrated post cardiac arrest care. Since 2002 two landmark study (HACA et al and Bernard et al) prove that therapeutic hypothermia in resuscitated patient with initial rhythm ventricular fibrillation improve their survival rate with good neurological outcome. (Passali, Pantazopoulos et al. 2011) found that nurses and doctors knowledge of basic and advanced life was suboptimal and practice is varied (Nick Truman et al. 2015). Therapeutic hypothermia implementation is low (Abella, Rhee et al. 2005). OBJECTIVE 1 To determine the level of knowledge of post cardiac arrest care among healthcare personnel in Emergency Department in Kelantan 2. To determine the level of practice of post cardiac arrest care among healthcare personnel in Emergency Department in Kelantan 3. To compare the mean of knowledge and practice of post cardiac arrest care among general, district and university hospital 4. To determine factors associated with the level of knowledge and practice of post cardiac arrest care among healthcare personnel in Emergency Department in Kelantan.METHADOLOGY The questionnaire is created based on 2010 AHA guidelines on CPR and ECC which has 3 domains, demographic, knowledge and practice had been validated. The study was a cross sectional study conducted for six months period from Jun till November 2015 in whole tenth of Emergency Departments in Kelantan. Sample size calculated is 156 and the respond rate was 155, 99%.Data was entered and analyzed via SPSS version 22. RESULT We enrolled 155 people with age range from 24 to 57 years old. Male population (52.9%) are more than female (47.10%).The mean knowledge score is 5.25 , while the mean practice score is 7.5. The median score of knowledge among workplace are different general hospital (6.0,Iqr 3) district hospital (5.0,Iqr 2) and university hospital (7,0 ,Iqr 3). In this study we found that five variables were statistically significant with knowledge score which were ACLS trained, position, workplace, place of practice, and number of patient with ROSC attended before. We also found that median practice score of respondent attended ACLS course and service duration is significantly different.CONCLUSION Healthcare personnel working in emergency department in Kelantan had low knowledge and average practice of post cardiac arrest care. The score of knowledge between districts, university and general hospital are different, however practice score are not. Previously attended ACLS course was found to be a significant factor for better knowledge and practice score. Workplace, place of practice, number of cardiac arrest patient with ROSC attended before and position of healthcare personnel was found to be a significant factor affecting knowledge of post cardiac arrest care. Service duration was found to be a significant factor for practice score.